Patterns and trends of pediatric and young adult computed tomography use in Brazil: 2008-2014 - Ana Cristina Murta Dovales; Tainá Olivieri Chaves; Paulo Roberto Valle Bahia; Marcela Brisighelli Schaefer; Bruna Bonaventura Failla; Lisa Suzuki; Marcelo Valente; Vinicius de Araújo Gomes; Luiz Antônio Ribeiro da Rosa; Mark Stephen Pearce; Lene Holanda Sadler Veiga (Brazilian Journal of Radiation Sciences)
ABSTRACT